2021
DOI: 10.1212/wnl.0000000000012601
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hospitalization and Death Associated With Pimavanserin Use in Older Adults With Parkinson Disease

Abstract: Objective:To determine the risk of hospitalization and death associated with pimavanserin use.Methods:We conducted a retrospective cohort study of adults 65 years and older with Parkinson’s disease between November 1, 2015 and December 31, 2018 using an administrative dataset on residents of Medicare-certified long-term care facilities and linked Medicare claims data. Propensity score-based inverse probability of treatment weighting (IPTW) was used to balance pimavanserin users and nonusers on 24 baseline char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 32 publications
0
51
0
1
Order By: Relevance
“…The incidence rates of falls and fractures were higher in the treatment groups when a diagnosis of psychosis was not required, perhaps because of the inclusion of some patients using antipsychotics off-label for treatment of non-psychosis symptoms. Related research of pimavanserin use in PDP has not required patients to have a psychosis diagnosis [ 27 , 30 ], but antipsychotics may frequently be used for the treatment of behavioral symptoms of dementia, sleep disorders, or other non-psychosis conditions [ 31 ]; thus, this sensitivity analysis may have also included additional patients using antipsychotics without true psychosis. Because of prescribing restrictions on pimavanserin, misclassified psychosis status may be more common in the comparator group.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rates of falls and fractures were higher in the treatment groups when a diagnosis of psychosis was not required, perhaps because of the inclusion of some patients using antipsychotics off-label for treatment of non-psychosis symptoms. Related research of pimavanserin use in PDP has not required patients to have a psychosis diagnosis [ 27 , 30 ], but antipsychotics may frequently be used for the treatment of behavioral symptoms of dementia, sleep disorders, or other non-psychosis conditions [ 31 ]; thus, this sensitivity analysis may have also included additional patients using antipsychotics without true psychosis. Because of prescribing restrictions on pimavanserin, misclassified psychosis status may be more common in the comparator group.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in projection analysis, the age groups higher than 50, also showed a relative rapid decline in PD mortality for the next decade. In general, PD progressed with age (Rani et al, 2022 ), for senior aged and late-stage PD patients, death may occur due to the disease itself or comorbidities (Bloem et al, 2021 ; Hwang et al, 2021 ). However, recent development in medication and non-medication therapies in PD has greatly improved the quality of life and life expectations of PD patients (Domingos et al, 2018 ; Raza et al, 2019 ).This may be associated with the decreasing trend of mortality in late age groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, while these studies were conducted in patients with schizophrenia and bipolar disorder, the FAERs data used in this study cannot accurately distinguish between the indications of various AAPs; hence we could not conduct analysis by underlying diagnoses. In addition, a retrospective cohort study of older adults with PD by Hwang et al reported that pimavanserin was associated with an increased risk of 30-day hospitalization compared to non-use ( 34 ). However, the study did not compare hospitalizations related to other AAPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study did not compare hospitalizations related to other AAPs. Therefore, the implication of its findings was thought to be limited by confounding with indication due to the lack of an active comparator ( 34 38 ). Given our study's findings of hospitalization safety signals related to commonly used off-label AAPs such as quetiapine, olanzapine, risperidone, and aripiprazole ( 39 ), a cohort study comparing individual AAPs may be needed to characterize the risk of hospitalization related to different AAP use compared to each other.…”
Section: Discussionmentioning
confidence: 99%